Cardiopulmonary transition in the neonate and infant at high altitude - Niermeyer, Susan; Shaffer, Elizabeth S.; Grindlay Moore, Lorna (Acta Andina, 2025)
Objective: Altitude-related alterations in arterial oxygen saturation (Sa O2), ventilation, and the pulmonary circulation occur during cardiopulmonary transition in the neonate and infant at high altitude. Design: Evidence gathered from original research and the published literature allows comparison of various population groups resident at high altitude in North and South American and Asia. Material and Methods: Data from pulse oximetry, respiratory plethymography, echocardiography, cardiac catheterization and histologic examination of neonates and infants illustrate alterations in function, instances of successful adaptation, and examples of morbidity and mortality related to birth or residence at high altitude. Results: Sa O2 falls with increasing altitude; however, this effect is not linearly related to altitude or barometric pressure. Sa O2 varies markedly with behavioral state. In contrast to patterns observed at sea level, Sa O2 decreases after 1 week of lifee in certain populations at high altitude. Periodic breathing in infancy increases in prevalence and duration at high altitude as compared to sea level. Periodic breathing occurs most commonly in active and quiet sleep and is associated with a cyclic pattern of oxygen saturation. Pulmonary artery pressure falls slowly after birth at extreme high altitude. At moderate high altitude, pulmonary artery pressures may normalize, but the pulmonary vascular bed remains susceptible to development of symptomatic pulmonary hypertension during a prolonged transition period. The syndrome of subacute infantile mountain sickness an persistence of right-to-left shunts at the foramen ovale and ductus arteriousus reflect elevated pulmonary artery pressure and pulmonary vascular resistance in infancy. Conclusion: The newborn infant at high altitude experiences a slower transition from fetal to mature patterns of cardiopulmonary function. Defferential effects occur with increasing altitude and differences in response are observed among various population groups at similar altitudes.